Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

17 Nov 2014, 03:50

Hi All,

I'm totally lost and unable to understand this question.

a) PareshGmat: where is this given in the question: Given that a + b + c = 3 * 4 = 12 .............. (1) b) MensaNumber: how did you get to this: S3 = 3*4 = 12 S2 = 2*3 = 6 So the third element of seq = 12 - 6 = 6 c) What does the third term mean? d) How have we assumed the first number in the sequence to be 1? Is it because that equation holds true for all positive numbers? But the series could start with say a 101!

Any help would be greatly appreciated!
_________________

Cheers!!

JA If you like my post, let me know. Give me a kudos!

Re: If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

17 Nov 2014, 05:33

1

This post received KUDOS

Approach: Back Solve

Steps: 1. start with C (6) 2. Is 6 product of subsequent numbers ? - yes 6=2 x3 3 Check other options before confirmation - none of them are products of subsequent number

If Sn is the sum of the first n terms of a certain sequence and if Sn = n(n+1) for all positive integers n, what is the third term of the sequence?

A. 3 B. 4 C. 6 D. 8 E. 9

Hi All,

I'm totally lost and unable to understand this question.

a) PareshGmat: where is this given in the question: Given that a + b + c = 3 * 4 = 12 .............. (1) b) MensaNumber: how did you get to this: S3 = 3*4 = 12 S2 = 2*3 = 6 So the third element of seq = 12 - 6 = 6 c) What does the third term mean? d) How have we assumed the first number in the sequence to be 1? Is it because that equation holds true for all positive numbers? But the series could start with say a 101!

Any help would be greatly appreciated!

We are told that the sum of a certain sequence is given by the formula Sn = n(n+1). So, the sum of the first 2 terms is S2 = 2(2+1) = 6, the sum of the first 3 terms is S3 = 3(3 + 1) = 12 and so on. Basically to get the sum of the first n terms we simply should substitute the value of n in the formula.

Re: If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

22 Nov 2014, 09:28

Bunuel wrote:

Basically to get the sum of the first n terms we simply should substitute the value of n in the formula.

Okay I get it now. We're taking the first term of the sequence to be 1, because the question states that Sn = n(n+1) for all positive values of n or the first n terms of the sequence. So the number which is best qualified to be the first term of the sequence is the lowest positive number i.e. 1, and the equation must be correct when we take n=1 and any increment to it.

I must concentrate much more while reading questions now!

If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

02 Dec 2014, 10:29

2

This post received KUDOS

1

This post was BOOKMARKED

Slightly different approach. Sn=n(n+1) now, suppose if the sequence has 1 term only. then sum will be equal to that term. so S1=first term put n=1 in the expression we have S1=1(1+1) =2 thus first term of the sequence =2 now S2=2(2+1)=6 we know that first term of the sequence =2, thus second term will be 6-2 =4 now, S3=3(3+1) =12, thus third term will be 12-first term - second term =12-2-4 =6

Re: If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

02 Dec 2014, 15:06

I guess my question is how is S2 different from the 2nd term conceptually. I know to those who get it, this might seem obvious but I don't understand how S2 is 6 and the 2nd term is 4.

ie isn't S2 = the 2nd term?

(I know once the light bulb clicks i'll be like "ohhhhhhh" but help me understand please)

manpreetsingh86 wrote:

Slightly different approach. Sn=n(n+1) now, suppose if the sequence has 1 term only. then sum will be equal to that term. so S1=first term put n=1 in the expression we have S1=1(1+1) =2 thus first term of the sequence =2 now S2=2(2+1)=6 we know that first term of the sequence =2, thus second term will be 6-2 =4 now, S3=3(3+1) =12, thus third term will be 12-first term - second term =12-2-4 =6

Re: If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

02 Dec 2014, 15:28

angelfire213 wrote:

I guess my question is how is S2 different from the 2nd term conceptually. I know to those who get it, this might seem obvious but I don't understand how S2 is 6 and the 2nd term is 4.

ie isn't S2 = the 2nd term?

(I know once the light bulb clicks i'll be like "ohhhhhhh" but help me understand please)

manpreetsingh86 wrote:

Slightly different approach. Sn=n(n+1) now, suppose if the sequence has 1 term only. then sum will be equal to that term. so S1=first term put n=1 in the expression we have S1=1(1+1) =2 thus first term of the sequence =2 now S2=2(2+1)=6 we know that first term of the sequence =2, thus second term will be 6-2 =4 now, S3=3(3+1) =12, thus third term will be 12-first term - second term =12-2-4 =6

No. S(2) would be the SUM of the first two terms in the sequence. We do not know what the sequence is. The sum is also represented by n(n+1) (eg. Sum of sequence = Sn = n(n+1)). Therefore, S2 = the sum of the first two numbers.

I guess my question is how is S2 different from the 2nd term conceptually. I know to those who get it, this might seem obvious but I don't understand how S2 is 6 and the 2nd term is 4.

ie isn't S2 = the 2nd term?

You are getting confused with the variables.

Usually,

Tn = nth term T1 = 1st term T2 = 2nd term and so on...

Sn = Sum of first n terms of the sequence Sn = 1st term + 2nd term + 3rd term + ... + nth term Sn = T1 + T2 + T3 + ....Tn

You are given here that "Sn is the SUM of first n terms..." So you have Sn = T1 + T2 + T3 + ....Tn = n(n+1)

So S1 = T1 S2 = T1 + T2 S3 = T1 + T2 + T3 and so on

Re: If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

20 Aug 2015, 22:52

MensaNumber wrote:

If Sn is the sum of the first n terms of a certain sequence and if Sn = n(n+1) for all positive integers n, what is the third term of the sequence?

A. 3 B. 4 C. 6 D. 8 E. 9

Sum of the first 'n' natural numbers=1/2 *n(n+1) That implies sum of the first 'n' even numbers =n(n+1) (2+4+6+8+....2n)=2(1+2+3+4+....+n) Therefore, the third term of sequence is 6 The correct option is C

If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

14 Nov 2015, 02:02

This question basically asks whether you know the shortcut formula for the sum of the first positive even integers which is n(n+1). So from the notation that Sn is the sum of ALL positives we derive that the first then should be 2, second - 4 and third even - is 6 and so on
_________________

Re: If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

16 Sep 2016, 06:48

NoHalfMeasures wrote:

If Sn is the sum of the first n terms of a certain sequence and if Sn = n(n+1) for all positive integers n, what is the third term of the sequence?

A. 3 B. 4 C. 6 D. 8 E. 9

let A1, A2, A3 be the first 3 terms Sum of first 2 terms = A1+A2 = 2(2+1) = 6 ..............(i) Sum of the three terms = A1+A2+A3 = 3(3+1) = 12 ......(ii)

(ii)-(i) = A3= 6
_________________

"Give without remembering, take without forgetting" - Kudos

If Sn is the sum of the first n terms of a certain sequence and if Sn = n(n+1) for all positive integers n, what is the third term of the sequence?

A. 3 B. 4 C. 6 D. 8 E. 9

We see that S3 = 3(4) = 12 and S2 = 2(3) = 6. Since S3 is the sum of the first three terms and S2 is the sum of the first two terms, the difference, S3 - S2 = 12 - 6 = 6, must be the value of the third term of the sequence.

Answer: C
_________________

Scott Woodbury-Stewart Founder and CEO

GMAT Quant Self-Study Course 500+ lessons 3000+ practice problems 800+ HD solutions

Re: If Sn is the sum of the first n terms of a certain sequence [#permalink]

Show Tags

16 Nov 2017, 09:09

As I understand it

Sn= sum of values all terms upto n Sn-1= sum of values of all terms upto n-1 therefore, does not include value of n. therefore value of n term= Sn-(Sn-1)

if Sn= n(n+1) then to find the value of 3rd term if we find the sum of first three term (upto 3rd term) and sum of first two terms (upto 2nd term) and then subtract it (S3-S2) which will give us the value of the 3rd term. S3=3(3+1)=12 n=3 S2=2(2+1)=6 n=2 S3-S2= value of third term = 12-6=6